Natriuretic Peptide-Guided Therapy in Chronic Heart Failure: A Meta-Analysis of 2,686 Patients in 12 Randomized Trials - Savarese, Gianluigi (Public Library of Science, 2013)
BACKGROUND: The role of cardiac natriuretic peptides in the management of patients with chronic heart failure (HF) remains uncertain. The purpose of this study was to evaluate whether natriuretic peptide-guided therapy, compared to clinically-guided therapy, improves mortality and hospitalization rate in patients with chronic HF. METHODOLOGY/PRINCIPAL FINDINGS: MEDLINE, Cochrane, ISI Web of Science and SCOPUS databases were searched for articles reporting natriuretic peptide-guided therapy in HF until August 2012. All randomized trials reporting clinical end-points (all-cause mortality and/or HF-related hospitalization and/or all-cause hospitalization) were included. Meta-analysis was performed to assess the influence of treatment on outcomes. Sensitivity analysis was performed to test the influence of potential effect modifiers and of each trial included in meta-analysis on results. Twelve trials enrolling 2,686 participants were included. Natriuretic peptide-guided therapy (either B-type natriuretic peptide [BNP]- or N-terminal pro-B-type natriuretic peptide [NT-proBNP]-guided therapy) significantly reduced all-cause mortality (Odds Ratio [OR]:0.738; 95% Confidence Interval [CI]:0.596 to 0.913; p = 0.005) and HF-related hospitalization (OR:0.554; CI:0.399 to 0.769; p = 0.000), but not all-cause hospitalization (OR:0.803; CI:0.629 to 1.024; p = 0.077). When separately assessed, NT-proBNP-guided therapy significantly reduced all-cause mortality (OR:0.717; CI:0.563 to 0.914; p = 0.007) and HF-related hospitalization (OR:0.531; CI:0.347 to 0.811; p = 0.003), but not all-cause hospitalization (OR:0.779; CI:0.414 to 1.465; p = 0.438), whereas BNP-guided therapy did not significantly reduce all-cause mortality (OR:0.814; CI:0.518 to 1.279; p = 0.371), HF-related hospitalization (OR:0.599; CI:0.303 to 1.187; p = 0.142) or all-cause hospitalization (OR:0.726; CI:0.609 to 0.964; p = 0.077). CONCLUSIONS/SIGNIFICANCE: Use of cardiac peptides to guide pharmacologic therapy significantly reduces mortality and HF related hospitalization in patients with chronic HF. In particular, NT-proBNP-guided therapy reduced all-cause mortality and HF-related hospitalization but not all-cause hospitalization, whereas BNP-guided therapy did not significantly reduce both mortality and morbidity.